INTRAGASTRIC INFECTION OF CONVENTIONAL AND GERM-FREE MICE WITH GIARDIA-LAMBLIA - Torres, MRF; Silva, MEC; Vieira, E. C.; Bambirra, E. A.; Sogayar, MIT; Pena, F. J.; NICOLI, JR (Associação Brasileira de Divulgação Científica (ABRADIC), 1992)
The effects of experimental infection with Giardia lamblia were studied in 30-day old conventional and germfree CFW mice (7 animals in each group) of both sexes. Cysts were observed in the feces of both groups 6 to 7 days after intragastric infection of each animal with about 2.5 x 10(5) G. lamblia trophozoites. Fecal cyst level was statistically higher in germfree mice (about 10(5) cysts/g feces) when compared with the conventional group (about 10(4) cysts/g feces). The peak of infection in the conventional group apparently occurred on the 10th day after infection as indicated by an increase of fecal weight and by histopathological examination. Intense infiltration of the lamina propria and high reactional hyperplasia of the lymphoid component were observed in the conventional group. There was no infiltration or hyperplasia in germfree infected mice and fecal weight was relatively constant throughout the experiment. These results suggest that, as is the case for other intestinal pathogenic protozoa, the intestinal microflora is indispensable for the expression of the pathogenicity but not for the multiplication of G. lamblia.
Keywords: GIARDIA-LAMBLIA; GERM-FREE MICE; CONVENTIONAL MICE